MODAL SOSIAL KELOMPOK TANI â€œCITAWAYAâ€ DI DESA TALIKURAN I, KECAMATAN SONDER, KABUPATEN MINAHASA - Stefanny Kristiany Kawulur; Benu Olfie L. S.; Agnes E. Loho (Sam Ratulangi University, 2017)
The objective of this research is to know sosial capital of â€œCitawayaâ€ farmer group in Village of Talikuran I, Sub-district of Sonder, Minahasa Regency. The study lasted for three months starting from February until April 2017. The data used are primary data collected through interviews on all members of farmer group â€œCitawayaâ€ which amounted to 20 people as respondents. Secondary data obtained from Talikuran I Village Offices. The analysis used is descriptive through Likert Scale and presented in tabular form. The results showed that â€œCitawayaâ€ farmer group in the Village of Talikuran I had a very high social capital of trust, social norms, social network, social values, and reciprocity by obtaining social capital index 85%. The highest social capital was trust indicators, then it followed by reciprocity indicators then social network indicators, then indicators of social values and recent indicators of social norms. The high social capital makes the â€œCitawayaâ€ farmer group able to survive until now and bring a good changing in the group.